Mental Health Support and Screening for Mood Disorders for Caregivers in the Neonatal Intensive Care Unit: Is the Call to Arms Being Answered? - Lagoski, Megan; Soghier, Lamia; Lagata, Joanne; Shivers, Miller; Sadler, Erin; Fischer, Elizabeth; Borschuk, Adrienne; House, Melissa; Children's Hospitals Neonatal Consortium Perinatal Mood Anxiety Disorder Focus Group (American Journal of Perinatology, 2024)
Objective Perinatal mood and anxiety disorders (PMADs) affect many neonatal intensive care unit (NICU) parents and are a significant risk factor for maternal suicide. Lack of screening and treatment interferes with infant development and bonding, compounding risks in fragile infants. We aim to describe PMAD screening in level IV NICUs across the Children's Hospitals Neonatal Consortium (CHNC) and to determine the relationship between standardized screening and mental health professionals (MHPs) presence.Study Design We surveyed experts at 44 CHNC NICUs about PMADs screening practices and presence of NICU-specific MHPs. Kruskal–Wallis test was used to examine relationships.Results Of 44 centers, 34 (77%) responded. Fourteen centers (41%) perform screening with validated tools. Thirteen (38%) centers have NICU-dedicated psychologists. Formally screening centers tend to have higher cumulative MHPs (p = 0.089) than informally screening centers. Repeat screening practices were highly variable with no difference in the number of cumulative MHPs.Conclusion Screening practices for PMADs vary across CHNC centers; less than half have additional MHPs beyond social workers. Creating a sustainable model to detect PMADs likely requires more MHPs in NICUs.Key Points
Keywords: perinatal mood and anxiety disorders; neonatology; health outcomes; neonatal intensive care unit; mental health support